Child dietary and eating behavior outcomes up to 3.5 years after an early feeding intervention: The NOURISH RCT. Issue 7 (19th May 2016) - Magarey, Anthea; Mauch, Chelsea; Mallan, Kimberley; Perry, Rebecca; Elovaris, Rachel; Meedeniya, Jo; Byrne, Rebecca; Daniels, Lynne
Abstract : Objective: To evaluate dietary intake impact outcomes up to 3.5 years after the NOURISH early feeding intervention (concealed allocation, assessor masked randomized controlled trial). Methods: In this study, 698 first‐time mothers with healthy term infants were allocated to receive anticipatory guidance on protective feeding practices or usual care. Outcomes were assessed at 2, 3.7, and 5 years (3.5 years post‐intervention). Dietary intake was assessed by 24‐h recall and Child Dietary Questionnaire. Mothers completed a food preference questionnaire and Children's Eating Behavior Questionnaire. Linear mixed models assessed group, time, and time × group effects. Results: There were no group or time × group effects for fruit, vegetable, discretionary food, and nonmilk sweetened beverage intake. Intervention children showed a higher preference for fruit (74.6% vs. 69.0% liked, P  < 0.001), higher Child Dietary Questionnaire score for fruit and vegetables (15.3 vs. 14.5, target ≥18, P  = 0.03), lower food responsiveness (2.3 vs. 2.4, of maximum 5, P  = 0.04), and higher satiety responsiveness (3.1 vs. 3.0, of maximum 5, P  = 0.04). Conclusions: Compared with usual care, an early feeding intervention providing anticipatory guidance regarding positive feeding practices led to small improvements in child dietary score, food preferences, and eating behaviors up to 5 years of age, but not in dietary intake measured by 24‐h recall.